The Limitations of Thematic Exegesis of Qur‘an - Al Hadeed, Rawan Fowzan Mufzi (Journal of Islamic and Religious Studies, 2018)
This study deals with the limitations of thematic exegesis of the Qur’ān. The main place where exegesis of the Qur’ān can be found remains the commentaries. In the majority of cases such commentaries start from the beginning of the first sūrah. In order to acknowledge the inputs and outputs in the Qur’ānic studies; explanation of the literary aspects of the verse, an account of its background and occasionally an interpretation of it with the help of another verse will be reviewed in this paper. In order to achieve the objectives of this study, scientists’ quotes will be critically examined.